Analisi comparativa del mercato dei dispositivi per incontinenza in cinque paesi europei - Cornago, Dante; Garattini, Livio (Farmeconomia. Health economics and therapeutic pathways, 2000)
The aim of the paper is to compare and valutate the market of the incontinence devices in five European countries: Italy, France, Germany, U.K. and Denmark. We chose incontinence devices because they are strictly connected with the development of the home delivery. France, Germany and U.K. has been analysed for their politic and territorial importance, while Denmark has been considered for its home assistance system. A common pattern has been applied in every country: first of all there is a general outline of the legislative aspect of the incontinence devices, then the study presents prescription procedure and the different models of distribution. Finally, it shows the competitive systems of the pharmaceuticals industry in every single country. The necessary information has been gathered through relevant literature and interviews with the area operators. The incontinence devices are repayable in all the studied countries, except from France. Every country has different health system (Italy, U.K and Denmark had a public health system; France and Germany has a mutualist health system). There isn’t an evident correlation between the type of the health system and the market of the incontinence devices.